PENGARUH SIKAP KEUANGAN TERHADAP PERILAKU MANAJEMEN KEUANGAN DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL INTERVENING PADA GENERASI Z DI DESA SLIWUNG KABUPATEN SITUBONDO - Rindayani, Rindayani; Wiryaningtyas, Dwi Perwitasari; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The purpose of this study was to determine effect of financial attitudes toward the locus of control, influence of financial attitudes towards financial management behavior, the influence of locus of control against financial management behavior, and the influence of financial attitudes towards financial behavior through the locus of control as an intervening variable. The research method in this study uses quantitative research. Data analyze and hypothesis testing in this study used structural equation model – (PLS-SEM). The result of the hypothesys test effect directly using Smart PLS 3.0, indicating that financial attitudes have a significant effect on the locus of control, financial attitudes significant influence the financial management behavior, and locus of control has a significant effect on financial management behavior. The result of hypothesis test of indirect influence showed financial attitudes towards financial managaement behavior through locus of control had a significant positive effect.